Locked Compression Plating for Peri‐ and Intra‐articular Fractures Around the Knee - Jain, Jitesh Kumar (Orthop Surg, 2013)
OBJECTIVE: To evaluate the role of locked compression plates (LCPs) in management of peri‐ and intra‐articular fractures around the knee. METHODS: Twenty distal femoral and 20 proximal tibial fractures were fixed with LCPs. The types of femoral fractures were A1 (four), A2 (three), A3 (two), C1 (one), C2 (seven) and C3 (three). The types of tibial fractures were A2 (one), A3 (two), B2 (two), C1 (four), C2 (five) and C3 (six). All patients were followed up for up to 18 months (mean, 12 months). Fourteen patients with distal femoral fractures and 19 with proximal tibial fractures underwent surgery using a minimally invasive percutaneous plate osteosynthesis (MIPPO) technique. The others were treated by open reduction. The average time of fixation was 8 days after injury (0–31 days). Knee Society scores were used for clinical and functional assessment. RESULTS: All fractures, except one of the distal femur and one of the proximal tibia, united. The mean union times for distal femoral and proximal tibial fractures were 15.2 and 14.9 weeks, respectively. One patient with a distal femoral fracture had implant failure. One patient was quadriplegic and did not recover the ability to walk. The average Knee Society scores of the remaining 18 patients were 82.66 (excellent) and 77.77 (functional score, good). There was one case of implant failure and one of screw breakage in distal femoral fractures. One case of nonunion occurred in a proximal tibial fracture. CONCLUSION: Provided it is applied with proper understanding of biomechanics, LCP is one of the best available options for management of challenging peri‐ and intra‐articular fractures.